2020
DOI: 10.31235/osf.io/nbv79
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modeling Reading Ability Gain in Kindergarten Children during COVID-19 School Closures

Abstract: By April 15th, 2020, more than 1.5 billion students worldwide experienced school closures in an effort to slow the spread of a novel coronavirus, COVID-19, during a worldwide pandemic [1]. These interruptions in formal educational experiences cause adverse consequences on school-age children’s academic outcomes [2]. We found that the kindergarten children without formal education would gain 67% less (2.41 vs 7.23 points/100 days) literacy ability compared to those with formal education. Compared to normal circ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 17 publications
4
34
0
4
Order By: Relevance
“…There are significant concerns regarding the loss of learning for children worldwide as a result of school closures (Bao et al 2020;Dorn et al 2020;OECD 2020). School closures are also likely to impact young children's social and emotional development (Buheji et al 2020;Giannini, Jenkins, and Saavedra 2020;UNESCO 2020b).…”
Section: Play In Early Childhood Education In the Context Of Covid-19mentioning
confidence: 99%
“…There are significant concerns regarding the loss of learning for children worldwide as a result of school closures (Bao et al 2020;Dorn et al 2020;OECD 2020). School closures are also likely to impact young children's social and emotional development (Buheji et al 2020;Giannini, Jenkins, and Saavedra 2020;UNESCO 2020b).…”
Section: Play In Early Childhood Education In the Context Of Covid-19mentioning
confidence: 99%
“…Fulfillment of these needs is the basis for children's proper development, and they are: "need to play, move, and relate with their peers" (OMEP, 2020, 120). Research (Bao, Qu, Zhang, and Hogan, 2020) found that kindergarten closures will reflect on the reduction in children's literacy by 67%, and as an attempt to alleviate this process the authors recommend daily reading of books to children. This is one of the bad effects of kindergarten closures.…”
Section: Kindergarten Teachersmentioning
confidence: 99%
“…This posed them to wages loss, subject them to unnecessary burdens and impacting their productivity negatively. Some parents who cannot abscond from their daily job had to leave their children alone at home and this can make them to wallow in immorality and other risky activities [22]. On the other hand, majority of families who were less privileged abandoned their children education during the long time that schools were closed down.…”
Section: Impact Of School Closure On Familiesmentioning
confidence: 99%
“…Many teachers (especially private school teachers) were not paid during the time schools were locked up. This made some of them to be unable to provide adequate needs for their families [22]. COVID-19 pandemic has created a lot of havoc in the lives of many teachers and they face a lot of psychological problems such as stress, fear, anxiety, depression, and insomnia that leads to lack of focus and concentration [21].…”
Section: Impact Of School Closure On Teachersmentioning
confidence: 99%